Revision of the fishfly genus Neochauliodes van der Weele (Megaloptera: Corydalidae) from India and adjacent regions of South Asia - Liu, Xingyue; Hayashi, Fumio; Yang, Ding (Zootaxa, 2010)
A revision of the fishfly genus Neochauliodes van der Weele from India and its adjacent regions in South Asia is presented. Seven species are recorded and re-described from Bangladesh, Bhutan, India, and Nepal, with one species described as new to science. A key to the adults of the Neochauliodes from South Asia is also given.